Phytochemical composition, total phenolic content and antioxidant activity of Anadara granosa (Linnaeus, 1758) collected from the east coast of South Sumatra, Indonesia (Baghdad Science Journal, 2023)
Anadara granosa is a species of the class bivalve commonly found on the east coast of South Sumatra as a fishery commodity. This species has not been widely studied as a source of new bioactive compounds that have antioxidant abilities. This study aims to analyze the antioxidant ability of A. granosa against DPPH radicals and its phytochemical profile qualitatively. Samples were taken at the fishing port of Sungsang Village, South Sumatra, Indonesia. Furthermore, the samples were extracted using ethanol as a solvent and tested for antioxidants against DPPH radicals, total phenol analysis, and preliminary phytochemical test. Based on the antioxidant test results, the IC50 value of the ethanolic extract of A. granosa was 85 g/ml with ascorbic acid 2 g/ml as a comparison. Then, the ethanol extract contained a total of 10.7057 mgGAE/g phenol and the results of the phytochemical test contained bioactive compounds of alkaloids, steroids, flavonoids, saponins, and tannins. The ethanolic extract of A. granosa contained bioactive compounds, which were reported to have potent antioxidant activity. The results of this study were expected to be important information in the latest report of the antioxidant activity of A. granosa species and contributed to the development of marine natural products.